Reaching skills in six-month-old infants at environmental and biological risk. - Liz Araújo Rohr (Public Library of Science (PLoS), 2021)
Objectives To assess kinematic parameters and proximal and distal reaching adjustments of infants at biological or environmental risk and compare with reaching performance of six-month-old full-term infants without known risk factors. Methods This blinded cross-sectional study included 62 infants at six months of age divided into three independent groups: Group with no known risk factor (NRF), 28 full-terms with no risk factors; Low SES group (LSES):19 full-terms classified as low socioeconomic status and no biological risk; Very preterm group (VPT), 15 very preterm infants at six months corrected age and no environmental risk. Infants were placed in a reclined baby chair at 45°, and a malleable and unfamiliar object was presented to the infant at 5-second intervals to elicit reaching movements. Results Infants from LSES presented reaching duration (p = 0.032, Cohen's f = 0.349) and movement unit (p = 0.033, Cohen's f = 0.351) significantly higher than VPT group. Horizontal hand orientation was moderately associated with infants at environmental risk (p = 0.031; Cramer's V = 0.30). Conclusion Infants of low socioeconomic status perform less functional reaching movements than very preterm infants at six months corrected age. Socioeconomic status may impact more on reaching skills than biological risk. Given the importance of reaching for infant development, low-cost public health strategies are needed to identify possible delays.